2010 Lomodrama - Grupo Teatro La Cochera (2017)
Dramaturgia: Silvia Villegas | Actúan: Graciela Mengarelli, Oscar Rojo | Iluminación: Fernando Castello | Objetos: José Quinteros | Sonido: Fernando Castello | Dirección: Paco Giménez | Consultado el 15 de enero de 2017 | http://www.alternativateatral.com/obra20057-lomodrama-dir-paco-gimenez